Search for supersymmetry using vector boson fusion signatures and missing transverse momentum in pp collisions at s $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector - The ATLAS collaboration; G. Aad; E. Aakvaag; B. Abbott; S. Abdelhameed; K. Abeling; N. J. Abicht; S. H. Abidi; M. Aboelela; A. Aboulhorma; H. Abramowicz; H. Abreu; et al. (Journal of High Energy Physics)
Abstract This paper presents a search for supersymmetric particles in models with highly compressed mass spectra, in events consistent with being produced through vector boson fusion. The search uses 140 fb −1 of proton-proton collision data at s $$ \sqrt{s} $$ = 13 TeV collected by the ATLAS experiment at the Large Hadron Collider. Events containing at least two jets with a large gap in pseudorapidity, large missing transverse momentum, and no reconstructed leptons are selected. A boosted decision tree is used to separate events consistent with the production of supersymmetric particles from those due to Standard Model backgrounds. The data are found to be consistent with Standard Model predictions. The results are interpreted using simplified models of R-parity-conserving supersymmetry in which the lightest supersymmetric partner is a bino-like neutralino with a mass similar to that of the lightest chargino and second-to-lightest neutralino, both of which are wino-like. Lower limits at 95% confidence level on the masses of next-to-lightest supersymmetric partners in this simplified model are established between 117 and 120 GeV when the lightest supersymmetric partners are within 1 GeV in mass.